Research progress of neuromyelitis optica spectrum disorders: Chinese scholars' reports published abroad - Jie-xi WEN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2016)
Neuromyelitis optica (NMO) is an inflammatory demyelinating disease of central nervous system (CNS), characterized by severe optic neuritis (ON) and transverse myelitis (TM). Since the discovery of NMO-immunoglobulin G (NMO-IgG), the definition of NMO has been changed greatly. Later, the concept of "neuromyelitis optica spectrum disorders (NMOSDs)" has been proposed. In recent years, more and more researches done by Chinese researchers were published on international journals. This review will focus on the work about NMO/NMOSDs done by Chinese researchers since 2010, in fields including the pathogenesis, relation between NMO-IgG and NMO/NMOSDs, diagnosis, treatment and gene detection.   DOI: 10.3969/j.issn.1672-6731.2016.09.003